Research on active defense application based on honeypot - Dequan YANG; Weimin LIU; Zhou YU (网络与信息安全学报)
Abstract：With the rapid development of financial information technology,cyber security events on the financial system have also increased greatly.Active defense plays an important role in improving the defense level of defined private network.How to quickly and effectively deploy and apply honeypot to capture and attack behavior,analyze the attack intention and raise the threshold of attack is the key to ensure the security of the defined private network.From the perspective of active defense,the advantage of honeypot active defense was analyzed,an active defense and defense filling passive defense integration was designed,and a honeypot within private network experimental environment was set up,the results show that the active defense technology can effectively improve the threshold of the attacker's attack,so as to improve the security level of the whole network.